To Study the Causative Organism Responsible for Corneal Ulcer In S.S.G Hospital Vadodara, Gujarat - Govind L Ninama; Jivraj R Damor; Navneet G Padhiyar; Tanuja B Javadekar (Medsci Publications, 2011)
Introduction: Number of blind people in the world is 45 million. Out of which 5.4 million blind people are in our country. Corneal ulcer is a major cause of blindness throughout the world. About 10% cases of blindness are due to corneal ulcer. Aims: To detect bacteria or fungus causing corneal ulcers and to give rapid presumptive diagnosis from direct smear examination. Study Design: 150 samples were collected during period of 1 year from clinically diagnosed cases of corneal ulcer at SSG Hospital, Baroda. The patients were of both sex and age groups varying from 2 to 70 years, outpatient department as well as indoor patients Study Period: one and half years Results: A total number of 150 patients presenting with suppurative keratitis were enrolled in the study from Ophthalmology department, SSG Hospital & Medical College, Baroda. Of the total 150 patients 99 (66%) were males & 51 (44%) were females with ulceration occurs in both group most frequently in the middle decades of life.